Field Ethics: Towards Situated Ethics for Ethnographic Research on the Internet - Estalella, Adolfo; Ardèvol, Elisenda (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2007)
This article reflects openly on the decisions that researchers have to deal with when undertaking qualitative research, especially ethnography, on the Internet. Our argument takes as starting point the ethical guidelines already developed for human subject research, and the way Internet researchers have tried to adapt these guidelines to their field. We argue that many of these ethical recommendations for researching the Internet have been designed according to specific applications (a chat, a mailing list, a blog, etc.), conferring specific properties to technology and making inferences about the kind of interaction that is taking place through such devices (public or private, for instance). We question these approaches and consider that the attribution of properties to technology restricts the scope of the ethical decisions that the researcher can make. We advocate a dialogical and situated ethical practice that takes into account every particular context when making any ethical decision during research. In line with this proposal, we report some ethical dilemmas that we have had to face in our own fieldwork on blogging practices among Spanish bloggers. We also draw on our experience of creating a "field blog" as part of our research. We describe three axes that have helped us to guide our ethical decisions in the field: the scope of individual data collected for participants in the course of research, the explicit and open presence of the researchers, and the search for symmetry and mutuality with our respondents in the field.URN: urn:nbn:de:0114-fqs070328